2009
DOI: 10.1099/mic.0.029017-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of capsular polysaccharide biosynthesis in Klebsiella pneumoniae clinical isolates

Abstract: Klebsiella pneumoniae is an enteric pathogen causing community-acquired and hospital-acquired infections in humans. Epidemiological studies have revealed significant diversity in capsular polysaccharide (CPS) type and clinical manifestation of K. pneumoniae infection in different geographical areas of the world. We have sequenced the capsular polysaccharide synthesis (cps) region of seven clinical isolates and compared the sequences with the publicly available cps sequence data of five strains: NTUH-K2044 (K1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
119
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(132 citation statements)
references
References 72 publications
10
119
0
1
Order By: Relevance
“…19 A cluster of genes are involved in capsule synthesis and driven by 2 promotors. 6 Previous studies have shown that 6 genes, galF, acidPPc, wzi, wza, wzb and wzc, are conserved among different capsular serotypes. 5,6 These conserved genes have also been proposed for the identification of capsular serotypes, including wzi and wzc.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…19 A cluster of genes are involved in capsule synthesis and driven by 2 promotors. 6 Previous studies have shown that 6 genes, galF, acidPPc, wzi, wza, wzb and wzc, are conserved among different capsular serotypes. 5,6 These conserved genes have also been proposed for the identification of capsular serotypes, including wzi and wzc.…”
Section: Discussionmentioning
confidence: 99%
“…6 Previous studies have shown that 6 genes, galF, acidPPc, wzi, wza, wzb and wzc, are conserved among different capsular serotypes. 5,6 These conserved genes have also been proposed for the identification of capsular serotypes, including wzi and wzc. 5,20 In this study, we have tried to elucidate the role of these conserved genes in virulence and whether they can function in a similar manner after exchanging a homologous gene from one serotype to another.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 While deletion of galF and acidPPC genes, which are driven by the P1 promoter, 13 had limited effect on virulence, the deletion of genes driven by the P2 promoter (wzi, wza, wzb, and wzc) exhibited moderate to high effects on virulence. The deletion mutants of the latter genes, which are responsible for surface assembly, CPS polymerization, and CPS production, also showed high susceptibility to neutrophilic phagocytosis and to serum.…”
mentioning
confidence: 99%